Protección social, un análisis frente a la evolución de la teoría del valor (2011)
The processes of social protection have been firmly related to the growing of capitalism, being justified by differences born in classes struggles due to values generation processes. But due to complex social, political and economic relationships existing below the productive process, the essential role of work in the formulation of value theory keeps confined in a mark of theories. Thus, the objective of the present document is that of identifying how the theory of value has being changing side by side with the evolution of economic systems and the way these changes have limited the mechanisms of social protection.